Las Universidades en el Perú: Análisis constitucional y legal desde su condición de Personas Jurídicas - Monge Morales, Gonzalo (2017)
Universities are special transcendent for the development of our country. However, very little attention has been taken into their legal regimen and the consequences derivate from their preexisting condition of legal entities and independent of the type of universities that constitute. Within the framework of the controversy generated by the new University Law (Law 30220), this article is enlightening in terms of its applicability, since the author presents his proposal based on a complete analysis of the universities, from a constitutional perspective, as from a legal and practical.